Dupuytren's disease: my personal view. (September 2017) - Warwick, D.
Dupuytren's disease is a heterogenous condition for which a palette of treatment options is required. Randomized control trial evidence is sparse; design challenges, such as validated outcome measures, blinding, equipoise, funding and assessment of recurrence, may limit further data accrual. Recurrence has different significance with different treatments and so rates are not directly comparable. The risk of any treatment is a function of both the chance of a complication and the clinical sequelae of that complication. The patient must be intimately involved in choosing treatment and is often trading rapid recovery for a higher chance of recurrence. Health economies are strained and as custodians of healthcare, surgeons should consider whether many patients even need treatment. To minimize the chance of complex, hazardous and expensive revision surgery, a low threshold for primary skin grafting should be applied, especially for those who are young, have dense disease or vulnerable genes.